2017
DOI: 10.1007/978-3-319-45833-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Approximations for the Chemical Master Equation: Comparison of the Method of Moments and the System Size Expansion

Abstract: The stochastic nature of chemical reactions involving randomly fluctuating population sizes has lead to a growing research interest in discrete-state stochastic models and their analysis. A widely-used approach is the description of the temporal evolution of the system in terms of a chemical master equation (CME). In this paper we study two approaches for approximating the underlying probability distributions of the CME. The first approach is based on an integration of the statistical moments and the reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…We observe that the approximations accurately capture the skewed distribution, with increasing accuracy at higher order. The figure is taken from [137].…”
Section: Construction Of Distributions From Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe that the approximations accurately capture the skewed distribution, with increasing accuracy at higher order. The figure is taken from [137].…”
Section: Construction Of Distributions From Momentsmentioning
confidence: 99%
“…numerical methods. The maximum entropy method for the construction of the marginal distributions of single species has recently been used in combination with moment closure methods and the system size expansion in [136,137]. Figure 7 shows the result for one example system.…”
Section: Construction Of Distributions From Momentsmentioning
confidence: 99%
“…The results revealed that the implications of a partially finite state space had not been completely understood in earlier studies and that the number of classical moment equations that are really needed is smaller than what was previously claimed. 11,12,35 The results of this paper can also be seen as the basis for a hybrid approach for the analysis of stochastic models of biochemical reaction networks. The binary variable representation of the network, and the derivation of moment equations from it, automatically keeps the full probability distribution over the finite part of the state space while resorting to low-order moments over the infinite part.…”
Section: Discussionmentioning
confidence: 93%
“…The dynamics of these processes is therefore well described by stochastic Markov processes in continuous time with discrete state space [15,22,42]. While few-component or linear-kinetics systems [16] allow for exact analysis, in more complex system one often uses approximative methods [12], such as moment closure [4], linear-noise approximation [3,9], hybrid formulations [25,26,33], and multi-scale techniques [38,39].…”
Section: Introductionmentioning
confidence: 99%